Eu3+ and Tb3+ coordination compounds with phenyl-containing carbacylamidophosphates: comparison with selected Ln3+ β-diketonates - Kariaka, Nataliia S.; Lipa, Aneta; Carneiro Neto, Albano N.; Malta, Oscar L.; Gawryszewska, Paula; Amirkhanov, Volodymyr M. (Frontiers in Chemistry, 2023)
Materials based on Eu3+ and Tb3+ coordination compounds are of great interest due to their strong red and green luminescence. Appropriate selection of ligands plays a huge role in optimizing their photophysical properties. Another very helpful instrument for such optimization is theoretical modelling, which permits the prediction of the emissive properties of materials through intramolecular energy transfer analysis. The ligands that allow for achieving high efficiency of Eu3+ and Tb3+ emissions include carbacylamidophosphates (CAPh, HL). In this brief review, we summarize recent research for lanthanides CAPh-based coordination compounds of general formulas Cat[LnL]4, [LnL3Q] and [Ln(HL)3(NO3)3], where Cat+ = Cs+, NEt4+, PPh4+ and Q = 1,10-phenanthroline, 2,2-bipyridine or triphenylphosphine oxide, involving the use of thermal gravimetric analysis, X-ray analysis, and absorption and luminescence spectroscopy. We carried out a comparison with selected Ln3+ β-diketonates. Possibilities and developments of theoretical calculations on energy transfer rates are also presented.